TEACHER CREATIVITY IN UTILIZING TECHNOLOGY AS A LEARNING MEDIA IN ELEMENTARY SCHOOLS - Ridwan; Murzal; Hurul In (Universitas Islam Negeri Mataram, 2024)
This study seeks to (1) describe MI Qubbatul Islam Cakranegara instructors' inventiveness in using audio-visual technology to teach the Qur'an and Hadith. (2) Assess MI Qubbatul Islam Cakranegara teachers' capacity to use audio-visual technology to teach the Qur'an and Hadith. Researchers employ qualitative methods—observation, interviews, and documentation of acquired data. Data analysis employed the Hamberman approach, which involves data reduction, display, conclusion, and verification. Data validity triangulates. Study results: (1) MI Qubbatul Islam Cakranegara provides many learning media that teachers can use. MI Qubbatul Islam Cakranegara has projectors, smart boards, laptops, PCs, wireless microphones, amplifiers, and funnel speakers. Audio-visual media at MI Qubbatul Islam Cakranegara increases learning quality and makes it more engaging. (2) Al-Qur'an Hadith teachers at MI Qubbatul Islam Cakranegara use audio-visual tools to enhance learning. Learning videos, audio murals, interactive presentations, and Islamic film documents are used in audio-visual media. Al-Qur'an Hadith teachers use audio-visual media to make learning more exciting and interactive and help students understand the material better and optimally. However, facilities are limited, so if the media is for one teacher, other teachers will clash with other classes. This medium has been shown to improve student comprehension and enthusiasm